Znikające świadectwo wielokulturowej tradycji miasteczek oraz ich lokalnego dziedzictwa na przykładzie pejzażu językowego Dzierżoniowa (Rychbach/Reichenbach). - Koszko, Marta (Scripta Neophilologica Posnaniensia, 2022)
The aim of this paper is to discuss the reasons for erasing the testimonies of the multicultural history of small towns and their local heritage. The concept of testimony in this article will refer to the linguistic landscape that is present in the public space and which comprises different types of signs produced by both private people and institutions. It has been assumed that the linguistic landscape can transfer the knowledge about intangible, immaterial aspects – information about social composition, the history of cross cultural relations in towns such as Dzierżoniów, and the knowledge about the coexistence of ethnically, culturally and linguistically diverse communities. Linguistic landscape can also transfer knowledge about multicultural tangible heritage, which encompasses cemeteries, gravestones, places of religious worship or manufacturing companies/factories. Despite its undeniable value one can observe that socio-cultural and political events and traumas, which affected Polish citizens, can lead to the almost complete erasure of linguistic landscape from the public space.